Supporting children with down's syndrome - Bentley, Lisa; Dance, Ruth; Morling, Elizabeth; Miller, Susan; Wong, Susan (Routledge, 2016)
This practical resource contains a wealth of valuable advice and tried-and-tested strategies for supporting children and young people with Down's Syndrome. Fully updated with the 2014 SEND Code of Practice, this text describes the different types of difficulties experienced by pupils with Down's Syndrome and helps practitioners to understand their diverse needs.